Peningkatan Kompetensi Pedagogik Guru melalui Kegiatan Supervisi Akademik - Zulfah, Hairani (YASIN, 2023)
The type of research used in this research is School Action Research (PTS). The purpose of this study was to improve the pedagogical competence of SD Negeri 2 Rumbuk teachers through academic supervision for the 2022/2023 academic year. In School Action Research (PTS) this was carried out in 2 cycles, from the results of the actions taken it was proven that the average results of the teacher's ability increased from cycles I and II, namely respectively 69.30 and ; 83,33. completeness achievement The ideal ability of teachers as a school group from cycle I and cycle II respectively, namely 33% increased to 100%. In terms of teacher activity, it was also obtained that teacher activity in coaching carried out by the Principal in applying the learning model in each cycle had increased. The results of this study indicate that academic supervision can improve the pedagogical competence of SD Negeri 2 Rumbuk teachers for the 2022/2023 school year with completeness reaching 100%.